Tanggungjawab Pemerintah Daerah Dalam Melindungi Orang Dengan Gangguan Jiwa - Souhoka, Vhanesya Claudya; Pattipawae, Dezonda Rosiana; Soplanit, Miracle (Pusat Studi Hukum dan Pemerintahan Fakultas Hukum Universitas Pattimura, 2024)
Mental disorders make a person disrupt their function and productivity so that they can disturb their family and society. The existence of ODGJ is seen roaming the A.Y Patty street area of Ambon City. There are some who are seen wearing makeshift and incomplete clothes, talking to themselves and even sleeping on the street and ODGJ who was pasung by the family, Wai Koi, a resident of Air Salobar, Nusaniwe District, has been confined by his family for decades. This writing uses the Normative Juridical research type, with a statutory approach and a conceptual approach. The results of the study show that the Regional Government must carry out legal protection for people with mental disorders in accordance with applicable regulations, in Law Number 17 of 2023 Article 77 paragraph 1D concerning health which states that